Pentatropis nivalis (J. F. Gmel.) D. V. Field & J. R. I. Wood (Apocynaceae): A new distribution record from Raigad District, Maharashtra, India - Phate, Preeti V.; Dhabushe, Sayali R.; Patil, Poonam R. (Plantae Scientia, 2026)
Pentatropis nivalis (J.F. Gmel.) D.V. Field & J.R.I. Wood (Apocynaceae) is reported here for the first time from Raigad District, Maharashtra, India, based on recent field collections from Revas Creek, Alibag taluka. This record extends the known distribution of the species within the state. The identification was confirmed through critical examination of diagnostic morphological characters and comparison with authentic taxonomic literature. Notes on habitat, associated plant species, and ecological conditions are provided.